Dapagliflozin therapy in type-2 diabetes: current knowledge and future perspectives. (February 2015) - Rizzo, Manfredi; Al-Busaidi, Noor; Rizvi, Ali A
<x xml:space="preserve">Abstract</x> Dapagliflozin is a new antidiabetic agent that belongs to the class of sodium glucose transporter 2 (SGLT-2) inhibitors. By decreasing renal glucose absorption, these agents target hyperglycemia independent of insulin secretion or insulin sensitivity. This unique mechanism of action differentiates them from existing antidiabetic agents currently on the market. It has been hypothesized that SGLT-2 inhibitors can be effectively and safely combined with other agents, including insulin, and incretin-based therapies. They can be used either as monotherapy, or in dual- or triple-agent combinations. Dapagliflozin has been shown to be effective and safe in patients with type-2 diabetes, with modest but significant reductions in HbA1c and a number of potentially beneficial and sustained non-glycemic effects, including those on body weight, plasma lipids and systolic blood pressure. In addition, dapagliflozin has been shown to have a generally favorable safety profile and is well tolerated. Ongoing studies may provide definitive answers on the cardiovascular safety and efficacy of SGLT-2 inhibitors in patients with type-2 diabetes.